Adjunctive antidepressant use and symptomatic recovery among bipolar depressed patients with concomitant manic symptoms: findings from the STEP-BD. - Goldberg, J; Perlis, R; Ghaemi, SN; Calabrese, JR; Bowden, C; Wisniewski, S; Miklowitz, D; Sachs, G; Thase, M (2007)
OBJECTIVE: Practice guidelines have advised against treating patients with antidepressants during bipolar mixed states or dysphoric manias. However, few studies have examined the outcomes of patients with co-occurring manic and depressive symptoms who are treated with antidepressants plus mood stabilizing drugs. METHOD: The authors compared outcomes in patients with bipolar disorder who received a mood stabilizing agent with versus without an antidepressant for a bipolar depressive episode accompanied by > or = 2 concurrent manic symptoms. The 335 participants were drawn from the first 2,000 enrollees in the National Institute of Mental Health (NIMH) Systematic Treatment Enhancement Program for Bipolar Disorder (STEP-BD). Kaplan-Meier survival curves and Cox regression models were used to compare time to recovery. General linear models examined the relationship between antidepressant use or mania symptom load at the study entry and mania or depression symptom severity at the 3-month follow-up. RESULTS: Adjunctive antidepressant use was associated with significantly higher mania symptom severity at the 3-month follow-up. The probability of recovery at 3 months was lower among patients with higher baseline depression severity. Antidepressant use neither hastened nor prolonged time to recovery once potential confounding factors were covaried in a Cox regression model. CONCLUSIONS: In bipolar depression accompanied by manic symptoms, antidepressants do not hasten time to recovery relative to treatment with mood stabilizers alone, and treatment with antidepressants may lead to greater manic symptom severity. These findings are consistent with those from the STEP-BD randomized trial for pure bipolar depression, in which adjunctive antidepressants did not yield higher recovery rates than did mood stabilizer monotherapy.